The Role of Peer-Assisted Learning Strategies (PALS) in Enhancing Students’ Reading Skills For Second Language Acquisition: Peran Strategi PALS dalam meningkatkan kemampuan reading siswa dalam pemerolehan bahasa kedua - Khusnul Harsul Lisan (Edu-Ling: Journal of English Education and Linguistics, 2022)
Reading becomes greatly important issue since it is considered as the most frequent input to develop second language acquisition. In reality, learning strategies used in the classroom activity often left a gap between the high proficiency students and the lower one. Hence, peer-assisted learning strategy (PALS) comes to provide a way out towards the gap. The role of peer-assisted learning strategy is assumed to be one of effective learning strategies since it gives them a more chance to interact and cooperate closely while diminish the gap itself in reading skills. Therefore, this research aimed to know the role of PALS in order to help the students enhancing reading skills focusing on the fluency, pronunciation, and word recognition in comprehending the texts while eliciting social interaction between them. This belongs to a case study research. The data were collected through interviews with various grades of students in senior high school. In the end, the research provided the descriptions about the students’ opinion towards the role of PALS in enhancing their reading skills.